Focusing on abuse, not use, in drug education. (December 2013) - Nicholson, Thomas; Duncan, David F; White, John; Stickle, Fred
<x xml:space="preserve">Abstract</x> How societies deal with drug use is premised on how drug abuse is defined and on distinguishing disordered drug abuse from non-disordered drug use. The Epidemiologic Catchment Area Study revealed that only 20.27% of consumers of illicit drugs in the United States experienced a period of abuse at some time during their drug use history, whereas among illicit drug users the current prevalence of substance abuse disorders was 4.19%. The persistent failure to differentiate use from abuse where currently illicit drugs are concerned undermines effective primary prevention of the addictive disorders we are really concerned with. Typical programmes have ignored this reality, which helps explain the failure of most drug education. Adolescents soon recognize the inaccuracies and exaggerations, which undermines the credibility of drug education and limits its effectiveness. The purpose of this article is to offer a more realistic strategy for drug education that focuses on the prevention of abuse rather than prevention of any and all use.